Estimating Economies of Scale and Scope with Flexible Technology - Thomas Triebs; David S. Saal; Pablo Arocena; Subal C. Kumbhakar (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2012)
Economies of scale and scope are typically modelled and estimated using cost functions that are common to all firms in an industry irrespective of whether they specialize in a single output or produce multiple outputs. We suggest an alternative flexible technology model that does not make this assumption and show how it can be estimated using standard parametric functions including the translog. The assumption of common technology is a special case of our model and is testable econometrically. Our application is for publicly owned US electric utilities. In our sample, we find evidence of economies of scale and vertical economies of scope. But the results do not support a common technology for integrated and specialized firms. In particular, our empirical results suggest that restricting the technology might result in biased estimates of economies ofscale and scope.
Keywords: D24; L25; L94; C51; 330; Economies of scale and scope; flexible technology; electric utilities; vertical integration; translog cost function; Skalenertrag; Verbundvorteil; Kostenfunktion; Schätzung; Technologie; Flexibilität; Kommunale Energiewirtschaft; Vertikale Konzentration; USA